(untitled) (Journal of Life and Earth Science, 2012)
Aggression behaviour in 160 adult Chakma tribal students was studied. The subjects were equally divided into boys and girls. Each category was again subdivided into early adolescent and late adolescent. Age of early adolescent group ranged from 11 to 14 years and late adolescent group ranged from 15 to 18 years. Thus, the study used a 2×2 factorial design representing two levels of gender (boy versus girl) and two levels of stage of development (early versus late adolescence). The measure of aggressive behaviour was administered on the sample for data collection. It was found that regardless of stage of development, boys expressed significantly higher rates of aggression than girls. Similarly, regardless of gender, respondents at early adolescent stage expressed significantly higher rates of aggression than the respondents at late adolescent stage. DOI: http://dx.doi.org/10.3329/jles.v6i0.9722 JLES 2011 6: 59-63